2022
DOI: 10.3390/cells11213462
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Attack Complex Mediates Retinal Pigment Epithelium Cell Death in Stargardt Macular Degeneration

Abstract: Recessive Stargardt disease (STGD1) is an inherited retinopathy caused by mutations in the ABCA4 gene. The ABCA4 protein is a phospholipid-retinoid flippase in the outer segments of photoreceptors and the internal membranes of retinal pigment epithelial (RPE) cells. Here, we show that RPE cells derived via induced pluripotent stem-cell from a molecularly and clinically diagnosed STGD1 patient exhibited reduced ABCA4 protein and diminished activity compared to a normal subject. Consequently, STGD1 RPE cells acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…ABCA4 is a membrane protein of the OS of PRs, however, cultured cells do not have an OS and some OS membrane proteins, like RHO 44 , are localized predominantly on the plasma membrane when heterologously expressed. ABCA4 has been reported to localize to the cell surface in HEK293T cells 40,45 , and in RPE cells derived from iPSCs 46,47 . Therefore, the plasma membrane localization of WT-ABCA4 and missense variants was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…ABCA4 is a membrane protein of the OS of PRs, however, cultured cells do not have an OS and some OS membrane proteins, like RHO 44 , are localized predominantly on the plasma membrane when heterologously expressed. ABCA4 has been reported to localize to the cell surface in HEK293T cells 40,45 , and in RPE cells derived from iPSCs 46,47 . Therefore, the plasma membrane localization of WT-ABCA4 and missense variants was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…70 Abca4 is also an important membrane-associated protein involved in retinal metabolism. 71 Relatively little is known about Btbd17 , but it is also expressed in the brain and is predicted to localize in the plasma membrane. 72 Genes expressed early in pseudotime that declined in expression during development included Btg1 , R3hdml , and Birc5 (survivin) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Eight days post-intervention, photoreceptor outer segment loss was noted and likely attributed to the deposition of membrane attack complexes on it. Prior studies have reported that the formation of membrane attack complexes on RPE cells leads to cell lysis [58,59]. At 9 days post-intervention, RPE loss and hypopigmentation were also observed.…”
Section: C3-overexpressed Mouse Modelmentioning
confidence: 86%